2005
DOI: 10.1074/jbc.m414276200
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Testican-2

Abstract: Mouse testican-2 was cloned, sequenced, and shown to be a proteoglycan with a multidomain structure closely similar to that of the human ortholog, previously described as a calcium binding extracellular matrix molecule of the BM-40/SPARC/osteonectin family (Vannahme, C., Schü bel, S., Herud, M., Gö sling, S., Hü lsmann, H., Paulsson, M., Hartmann, U., and Maurer, P. (1999). J. Neurochem. 73, 12-20). Recombinant mouse testican-2 was used to prepare specific antibodies that allowed the detection of testican-2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 26 publications
1
39
0
1
Order By: Relevance
“…Similarly, CYFIP2 has been shown to negatively modulate survival of colon cancer cells (37). Epigenetic inactivation of SPOCK2 gene is involved in malignant transformation of ovarian endometriosis (38,39). Interestingly, PYGO1 and BCL9L, hypermethylated in metastatic PPGL, participate in the nuclear b-catenin/TCF complex.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CYFIP2 has been shown to negatively modulate survival of colon cancer cells (37). Epigenetic inactivation of SPOCK2 gene is involved in malignant transformation of ovarian endometriosis (38,39). Interestingly, PYGO1 and BCL9L, hypermethylated in metastatic PPGL, participate in the nuclear b-catenin/TCF complex.…”
Section: Discussionmentioning
confidence: 99%
“…The NDRG2 gene is part of a fourmember gene family whose members are involved in cell differentiation, and NDRG2 has been shown to be expressed in the embryonic ventricular zone as well as in neurogenic regions in adult brain (Okuda and Kondoh, 1999). Also downregulated was sparc/ osteonectin, cwcv and kazal-like domains proteoglycan 2 (SPOCK2), an extracellular protein also known as testican-2, which has functions that include regulation of protease activity (Nakada et al, 2003) and neurite outgrowth (Schnepp et al, 2005). Finally, semaphorin 3G (SEMA3G) was also identified as being downregulated in BMEC cultures and while little is known about this semaphorin isoform, it has been shown to have involvement in axonal guidance through neuropilin-2 (Taniguchi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the initial screen of ES cells demonstrated that message was present for a wide variety of PG core proteins, including many that have been shown to have tightly regulated spatiotemporal distribution in vivo. These include HSPG syndecan 3 and chondroitin sulfate proteoglycans (CSPGs) testican [24] and leprecan [25]. However, the CSPG NG2, often used as a neural-specific marker [26], was found only in the day 7 cells (both GFP-positive and GFP-negative).…”
Section: Differential Changes In Gene Expressionmentioning
confidence: 99%